Geographic, Network, and Competitor Social Cues: Evidence from U.S. Venture Capitalists Internationalization Decisions. (10th April 2017) - Vedula, Siddharth; Matusik, Sharon F.
Abstract : Research summary: We examine how social cues drive strategic decision making under uncertainty, specifically in the context of U.S. VC firms' first internationalization decisions. We compare the relative impacts of cues from: (a) geographically proximal firms, (b) syndicate partners, and (c) VCs investing in the same industries as the focal firm. Over the 23‐year period from 1990 to 2012, we find that cues from geographically proximal peers are important, while syndicate partner actions play a significant but smaller role in driving focal firm internationalization decisions. Analogous, firm‐specific experience in the form of nonlocal (but domestic) investing attenuates the effect of geographically proximal peers. Our findings have important implications on how the nature of information from social cues affects imitation decisions. Managerial summary: The U.S. venture capital industry has globalized rapidly over the past two decades, but the decision to invest abroad is still a highly uncertain one, particularly for firms with no prior global experience. We examine the extent to which such initial internationalization decisions are driven by social cues, comparing the relative impacts of social cues from: (a) geographically proximal firms, (b) syndicate partners, and (c) VCs investing in the same industries as the focal firm. We find that the foreign investment decisions of geographically proximal peers have the strongest impact, while syndicate partner actions play a smaller role. The impacts of geographically proximal peers are also weaker for firms that have analogous experience, in the form of nonlocal (but domestic) investing. Copyright © 2017 Strategic Management Society